Characteristics of microbial activity in atmospheric aerosols and its relationship to chemical composition of PM2.5 in Xi'an, China. (August 2020) - Wang, Beibei; Li, Yanpeng; Xie, Zhengsheng; Du, Shengli; Zeng, Xuelin; Hou, Junli; Ma, Tianfeng
Abstract: Microbial activity levels in atmospheric aerosols can affect human health, and ecosystem and atmospheric processes. However, information on the influence of microbial activity in atmospheric aerosols remains very limited. In this study, the characteristics of microbial activity in atmospheric aerosols in Xi'an, China, were determined using the fluorescein diacetate hydrolysis method. The influences of meteorological factors, height and water-soluble inorganic ions on microbial activity were examined. The results indicate that the levels of the atmospheric inorganic ions increased as the air quality index (AQI) increased. The microbial activity and concentration of PM2.5 were significantly positively correlated during sampling period ( p < 0.05). Notably, microbial activity levels in PM2.5 and PM10 both increased with the AQI and decreased from ground level to 228 m. Additionally, higher microbial activity levels were detected during floating dust events and lower levels were found during periods of rainfall. Among the nine inorganic ions, microbial activity was significantly positively correlated with Na +, Mg 2+ and Ca 2+ ( p < 0.05). Correlation results indicate that microbial activity was greatly influenced by soil source in spring and summer. The present results improve our understanding of the correlations between airborne microbes and atmospheric chemical composition. Graphical abstract: Image 1 Highlights: Microbial activity and atmospheric inorganic ions both increased with AQI. Microbial activity was higher during dust events and lower during rainfall. Microbial activity decreased significantly from ground level to 228 m. Microbial activity was greatly affected by soil source in spring and summer.